MR Findings in Hashimoto Encephalopathy - Song, Yonung Min; Seo, Dae Won; Chang, Gregory Youngnam (American Journal of Neuroradiology, 2004)
Summary: A 35-year-old Korean woman had Hashimoto encephalopathy of varying MR imaging appearance over 5 years that ranged from that of transient subcortical ischemia to that of gradually evolving multifocal signal intensity change accompanied by unilateral cerebellar atrophy. Thus, the MR imaging appearance of Hashimoto encephalopathy may simulate an ischemic stroke, multiple tumors or granulomas, or even a degenerative process.